Investigating working memory updating processes of the human subcortex using 7T MRI - Anne C Trutti; Zsuzsika Sjoerds; Russell J Boag; Solenn LY Walstra; Steven Miletić; Scott JS Isherwood; Pierre-Louis Bazin; Bernhard Hommel; Sarah Habli; Desmond HY Tse; Asta K Håberg; Birte U Forstmann (eLife)
A growing body of research suggests that dopamine is involved in working memory updating and that the striatum takes up a critical role in the subprocess of working memory gating . In this study, we investigated subcortical – in particular, possible dopaminergic – involvement in working memory updating subprocesses using the reference-back task and ultrahigh field 7 Tesla functional magnetic resonance imaging (fMRI). Using a scanning protocol optimized for BOLD sensitivity in the subcortex, we found no evidence of subcortical activation during working memory gate opening, predominantly activations in frontoparietal network regions, which challenges the idea of a striatal gating mechanism. However, during gate closing, subcortical activation was observed. Furthermore, a ready-to-update mode demonstrated large-spread subcortical activation, including basal ganglia nuclei, suggesting that the basal ganglia are engaged in general updating processes rather than specifically controlling the working memory gate. Moreover, substituting new information into working memory elicited activation in dopamine-producing midbrain regions along with the striatum, thalamus, and prefrontal cortex, indicating engagement of the basal ganglia-thalamo-cortical loop possibly driven by (potential) dopaminergic activity. These findings expand our understanding of subcortical regions involved in working memory updating, shifting the focus from gate opening to substitution as a midbrain-driven updating process.